The construction, deconstruction, and reconstruction of crime news: a case study of Malaysian newspapers - Azman Azwan Azmawati,; Muhammad Raqib Mohd Sofian,,; Shuhaida Md Noor,; Juliana Abdul Wahab, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Mass media has become an important agent of socialization by reproducing dominant and other social norms, beliefs, discourses, ideologies, and values. Although the media can be considered as an educator, most of the transmission of norms, beliefs, ideologies, discourses, and values occur in an unconscious manner. In essence, the media will select and process facts for the public. Because they do this so systematically, they can affect the way their audience is influenced by the delivered information. Thus, the portrayal of crime in the news media has played a crucial role in creating public awareness and planting seeds of concern regarding crimes in Malaysia. How crime is presented in the media and how the media capitalizes on crime news can affect how society perceives crime. The presentation of crime news in the media is the result of a complex process of news gathering and news production. Hence, it is crucial to understand how crime news is produced and presented, and the impact this type of news has on society. It will in turn help to shape public opinion and public policy, which could consequently become a national concern. This paper presents an analysis of the hidden messages that the media is forwarding to society and the priorities given in constructing crime news in the local media. This study has analyzed news texts to understand how different types of crimes are covered and reported. An analysis of news narratives is also presented to understand how crimes are constructed and portrayed by the Malaysian media.